Test of a serial mediated model of green human resource management in the manufacturing industry - Nosrati, Saeid; Talebzadeh, Niusha; Maydon, Denitsa Hristoforova; Karatepe, Osman M. (Wiley, 2025)
Our paper develops and tests a serial mediated model of green human resource management (GHRM). Data came from entry-level employees and supervisors in the power manufacturing industry in Bulgaria. The results from PROCESS Macro suggest that egoistic value, altruistic value, and biospheric value completely mediate the link between GHRM and eco-friendly behavior (ECB). The impact of GHRM on ECB is completely mediated by environmental empathy. More importantly, egoistic value, altruistic value, or biospheric value and environmental empathy completely and serially mediate the link between GHRM and ECB. The abovementioned findings enhance the current knowledge on the mediators that operate in the association between GHRM and ECB. The results will assist policymakers, businesses, and scholars in understanding the significance of GHRM in the international marketplace as well as the underlying associations between GHRM and ECB, serving as a valuable tool for fostering and attaining these behaviors in the manufacturing industry.
Keywords: eco-friendly behavior; environmental empathy; environmental values; green human resource management; sustainability